2018
DOI: 10.1093/mnras/sty2988
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of colour and polarimetric variability of RW Aur A in 2010–2018

Abstract: Results of U BV RIJHKLM photometry and V RI polarimetry of a young star RW Aur A observed during unprecedented long and deep (up to ∆V ≈ 5 mag) dimming events in 2010-11 and 2014-18 are presented. The polarization degree p of RW Aur A at this period has reached 30 per cent in the I band. As in the case of UX Ori type stars (UXORs), the so-called 'bluing effect' in the colour-magnitude V versus V − R c , V − I c diagrams of the star and a strong anticorrelation between p and brightness were observed. But the du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 70 publications
(136 reference statements)
7
31
0
Order By: Relevance
“…We find good agreement with the observations for a max ∼ 150 µm, Q tot = Q abs + 0.12Q sca (green curve in the bottom panel of Fig. 7); the effective albedo is ∼ 0.7 in the visual range, consistent with the polarimetry results analysed most recently by Dodin et al (2019). If the scattering is less efficient, a max needs to be larger.…”
Section: Extinction Due To the Dimming Layersupporting
confidence: 91%
See 2 more Smart Citations
“…We find good agreement with the observations for a max ∼ 150 µm, Q tot = Q abs + 0.12Q sca (green curve in the bottom panel of Fig. 7); the effective albedo is ∼ 0.7 in the visual range, consistent with the polarimetry results analysed most recently by Dodin et al (2019). If the scattering is less efficient, a max needs to be larger.…”
Section: Extinction Due To the Dimming Layersupporting
confidence: 91%
“…The first hypothesis is a dust-laden wind (e.g. Petrov et al 2015;Dodin et al 2019). Facchini et al (2016) (and earlier France et al 2014 have detected narrow absorption lines at ∼ −60 km s −1 in the optical Na and K doublets, and in the N i, Si ii, and Si iii UV lines.…”
Section: Origin Of the Dimming Eventsmentioning
confidence: 98%
See 1 more Smart Citation
“…The light curves and the color evolution of V582 Aur show striking similarity to those of an other well known young stellar object, RW Aur A (Dodin et al 2019, and the references therein). The physical reason for the behavior of RW Aur A is still debated.…”
Section: Nature Of the Obscuring Materialssupporting
confidence: 59%
“…The authors assumed that decreases in brightness in the visible range were caused by the appearance of hot dust in the disk wind of RW Aur A at a temperature of about 1000 K. A similar interpretation was previously proposed by Grinin et al (2009) to explain the deep minimum of the T Tauri star V1184 Tau, where the decrease in brightness in the optical range with constant or slightly increased emission in the K band was caused by an increase in the disk thickness near the dust evaporation zone as a result of amplification of the disk wind. Dodin et al (2019) recorded a significant increase in the linear polarization of RW Aur A during deep minima in 2010-2011 and 2014-2018. The value and orientation of the polarization vector indicated that the star and inner regions of the accretion disk were shielded by the axial symmetric dusty disk wind.…”
Section: Wind and Circumstellar Dustmentioning
confidence: 95%